The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.571064
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing and Bioinformatic Analysis of Environmental, Agricultural, and Human Campylobacter jejuni Isolates From East Tennessee

Abstract: As a leading cause of bacterial-derived gastroenteritis worldwide, Campylobacter jejuni has a significant impact on human health in both the developed and developing worlds. Despite its prevalence as a human pathogen, the source of these infections remains poorly understood due to the mutation frequency of the organism and past limitations of whole genome analysis. Recent advances in both whole genome sequencing and computational methods have allowed for the high-resolution analysis of intraspecies diversity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…This indicates that these clinical isolates likely originated from poultry or cattle sources, which further supports the inference that poultry has a relatively higher contribution to C. jejuni infection than cattle. When examining clinical and environmental C. jejuni isolates collected from east Tennessee during the same time period, Kelley et al observed that the clinical isolates clustered with isolates from cattle, chickens, water, and other birds [65], which is consistent with our findings. Using three different types of data (MLST, comparative genomic fingerprints, and 15 host segregating genes) for source attribution, Thepault et al concluded that 31-63% of the British and French clinical cases of C. jejuni could be attributed to chicken while 22-55% were attributed to ruminants [24].…”
Section: Jejuni Associated With Poultry and Bovine Sourcessupporting
confidence: 91%
See 2 more Smart Citations
“…This indicates that these clinical isolates likely originated from poultry or cattle sources, which further supports the inference that poultry has a relatively higher contribution to C. jejuni infection than cattle. When examining clinical and environmental C. jejuni isolates collected from east Tennessee during the same time period, Kelley et al observed that the clinical isolates clustered with isolates from cattle, chickens, water, and other birds [65], which is consistent with our findings. Using three different types of data (MLST, comparative genomic fingerprints, and 15 host segregating genes) for source attribution, Thepault et al concluded that 31-63% of the British and French clinical cases of C. jejuni could be attributed to chicken while 22-55% were attributed to ruminants [24].…”
Section: Jejuni Associated With Poultry and Bovine Sourcessupporting
confidence: 91%
“…This was consistent with results based on isolates from Scotland reported by Sheppard et al, with the exceptions of ST-48 (multiple), ST-206 (cattle/sheep), ST-464 (N/A), and ST-52 (multiple) CCs [66]. This was also similar to results based on isolates from east TN described by Kelley et al with the exception of ST-48 (cattle), ST-206 (N/A), ST-22 (N/A), and ST-52 (N/A) CCs [65]. Some of these differences may be due to geospatial variability in host adaptation.…”
Section: Jejuni Associated With Poultry and Bovine Sourcessupporting
confidence: 88%
See 1 more Smart Citation
“…Poultry has been reported as the main source of human infection in studies carried out in different locations including Denmark ( Joensen et al, 2020 ), Sub-Saharan Africa ( Gahamanyi et al, 2020 ), or Lithuania ( Ramonaite et al, 2017 ). On the other hand, other authors have identified as important sources of human infection both chicken and ruminants in France ( Berthenet et al, 2019 ), the United States ( Kelley et al, 2020 ), Israel ( Rokney et al, 2018 ), and Sub-Saharan Africa ( Hlashwayo et al, 2020 ) or chicken and wild birds in Baltic countries ( Mäesaar et al, 2020 ). Moreover, the detection of no major differences in the resistance profiles among isolates from different points of the chicken meat processing chain ( Dramé et al, 2020 ) suggests that AR spread is originated on upstream steps, such as the animal feeding, where the animals are exposed to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental and clinical isolates of C. jejuni were isolated from a previous study (Kelley et al, 2020). Whole genomes were uploaded to KBase and their genomes were annotated to the 81-176 wild-type genome.…”
Section: Abundance Of Slip Within Environmental and Clinical Isolatesmentioning
confidence: 99%